Ozone therapy and kinesiology effectiveness in the COVID-19 aftermath. Yaguaramas, 2022 - Maydelin Pérez Reina; Maria Caridad Pérez Reina; Jorge Enrique Rodríguez León; Elizabeth Núñez Pérez; Isidro Lamote Matos; Idalmis Valero Valero (Medisur)
Foundation: rehabilitation is a pillar for the post-COVID-19 patients’ recovery. The study and analysis of the ozone therapy and kinesiology effects can contribute to the accumulation of evidence that will never be enough to face a disease like COVID-19. Objective: determine the ozone therapy and kinesiology effect in the consequences of COVID-19 treatment. Methods: a quasi-experimental intervention study was carried out in 44 convalescent COVID-19 patients with a diagnosis of any sequelae, who attended the Yaguaramas health area multidisciplinary consultation, from January to December 2021, and received ozone therapy and kinesiology treatment. The studied variables: sex, age, sequelae, health status and functional independence; these last two, before and after treatment. Results: the female sex predominated (77.3%), ages between 50-54 years (27.3%); and peripheral polyneuropathy (81.8%) was the most frequent sequelae. 88.6% of patients considered a significant health impairment before treatment; After this, 68.2% did not consider any health impact. Before treatment, low dependence was determined in 61.4% of patients; after treatment, 79.5% were independent. Conclusions: ozone therapy and kinesiology in COVID-19 convalescent patients proved to be safe and effective treatment alternatives.